Psycho-Sufistic Approach in Islamic Counseling: Strengthening The Spiritual Well-Being Of Santri - Muhamad Rozikan; Mungin Eddy Wibowo; Edy Purwanto; Mulawarman Mulawarman (International Conference on Science, Education, and Technology, 2021)
Every santri (student in an Islamic boarding school) has the same rights in achieving education, attention, and affection. All pesantren (Islamic boarding schools) ideally encourage santri to develop spiritual well-being. However, not all pesantren provide psycho-Sufistic counseling. This descriptive qualitative study aims to describe the implementation of psycho-Sufistic Islamic counseling at pesantren Qudsiyah Kudus. The data analysis was carried out through data collection, data reduction and categorization, data display, and conclusion. This study found that implementing Islamic counseling with a psycho-Sufistic approach at pesantren Qudsiyah Kudus could strengthen four domains of spiritual well-being santri, namely personal, communal, environmental, and transcendental. In the personal domain, santri showed sensitivity to self-identity, self-awareness, happiness in life, inner peace mentally and spiritually, and making sense of life. While in the communal domain, santri developed in terms of loving someone, forgiving others, believing in others, respecting others, and doing good to others. In addition, from the environmental domain, santri transformed the characters of uniting with nature, be amazed by God's creatures, blend with the natural environment, feel a sense of wonder with the environment, and harmony with the environment. Lastly, from the transcendental domain, santri improved spirituality such as worship God, pray to God, have faith in God, always being grateful, and praying for God's pleasure.